Older People Living Alone and Their Strategies to Face Life: Case Studies from Yogyakarta and West Sumatra - Insriani, Hezti; Mitra, Robi; Schröder-Butterfill, Elisabeth (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Across Indonesia, the dominant model for care and support in later life is for older people to live with or near younger family members. However, coresidence with an adult child or other close relative is not always attainable or preferred. There are conditions where older people live alone and cannot fully depend on their family members for care and support, be it for matters related to physical, economic, psychological, or spiritual needs. We examine how older people who live alone, live their lives and what strategies they pursue in facing life. The data presented in this paper are a subset of a larger comparative study on Older People’s Care Networks, which covered five disparate sites across Indonesia. This article focuses on evidence from West Sumatra and Yogyakarta. As our case studies illustrate, older people living alone is a diverse category, ranging from those with children, to those who are de facto childless or actually childless. Their security or vulnerability cannot simply be deduced from their household composition, but they require the understanding of how people create, maintain, and develop supportive networks and how they use agency in actively managing dependence, independence, and interdependence over the life course and in later life.